Social enterprise in Ukraine - Dubyk, Kateryna; Pozniakova, Olena (Видавництво Львівської політехніки, 2013)
Social entrepreneurship is the solution of socioeconomic problems of society. This is a new phenomenon in Ukraine, which could be of great benefit. European state financed a project to promote social entrepreneurship in order to further this information. Modern development of social enterprises requires intervention of the state. Legislative regulation and balance between the objectives of enterprises and society are necessary.
Keywords: social entrepreneurship; non-state unprofitable organization; public interest; commercial interest; income